2019
DOI: 10.1093/mnras/stz1636
|View full text |Cite
|
Sign up to set email alerts
|

Triage of astrometric binaries – how to find triple systems and dormant black hole secondaries in the Gaia orbits

Abstract: Preparing for the expected wealth of Gaia detections, we consider here a simple algorithm for classifying unresolved astrometric binaries with main-sequence (MS) primary into three classes: binaries with a probable MS secondary, with two possible values for the mass ratio; probable hierarchical triple MS systems with an astrometric secondary as a close binary, with a limited range of mass-ratio values; and binaries with a compact-object secondary, with a minimal value of the mass ratio. This is done by definin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…( 8), we will call the expression with α the observational AMRF or just A and the right-most expression the theoretical AMRF. As Shahaf et al (2019) showed, the AMRF is a useful parameter for separating BH systems from non-degenerate systems, as we also show in Sect. 5.2.…”
Section: Identifying the Ob+bh Systemssupporting
confidence: 63%
See 2 more Smart Citations
“…( 8), we will call the expression with α the observational AMRF or just A and the right-most expression the theoretical AMRF. As Shahaf et al (2019) showed, the AMRF is a useful parameter for separating BH systems from non-degenerate systems, as we also show in Sect. 5.2.…”
Section: Identifying the Ob+bh Systemssupporting
confidence: 63%
“…The next step is to separate the needles -the OB+BH systems -from the haystack -normal binaries with two main-sequence components. For this, we used the method described by Shahaf et al (2019). Their method astrometrically identifies binaries with a compact object, based on the observed astrometric signal of the binaries.…”
Section: Identifying the Ob+bh Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carmichael et al 2021), radial velocity studies (e.g. Shahaf & Mazeh 2019), and microlensing observations (e.g. Han et al 2016;Poleski et al 2017) of main-sequence stars show that substellar objects exist in orbits of ∼ 1 AU.…”
Section: Introductionmentioning
confidence: 99%
“…While there is clearly much to be learned about astrometric binaries in which both stars are luminous, here we are interested in the rarer cases of luminous stars hosting dark companions such as black holes (BH). Several previous studies have focused on the population of unseen BH binaries with orbital periods shorter than Gaia's lifetime (Mashian & Loeb 2017;Breivik et al 2017;Yamaguchi et al 2018;Yalinewich et al 2018;Yi et al 2019;Shahaf et al 2019;Wiktorowicz et al 2020;Shikauchi et al 2020). These studies have been motivated in part by recent claimed detections of such detached BH binaries, both in the field (Thompson et al 2019;Liu et al 2019;Rivinius et al 2020;Jayasinghe et al 2021) and in globular clusters (Giesers et al 2018(Giesers et al , 2019.…”
Section: Introductionmentioning
confidence: 99%